CONTRADICTIO IN ADIECTO, CZYLI NA ILE TO, CO JEST OCZYWISTE, WYMAGA ZASADNICZEJ WYKŁADNI PRAWA - Kochanowski, Janusz (Wydział Prawa i Administracji UAM, 2009)
Until recently the “obvious groundlessness” of a motion or a complaint has been understood both in the case law and jurisprudence as decidable prima facie, using the basic legal knowledge. However, the Supreme Court in the resolution of 20 December 2007, registered in the book of legal principles, included a fundamental interpretation of the meaning of “obvious groundlessness” in the context of a motion aimed to allow penal responsibility of a judge who applied retroactive rules deciding penal cases based on the martial law decree. As a result, the concept of “obvious groundlessness” has lost its previous meaning involving penal responsibility of judges and it might now be understood as including more complex issues which require fundamental interpretation of the statute. This construction constitutes a logical fallacy of contradictio in adiecto. The resolution shifts the burden of deciding the merits of granting the leave for penal responsibility of a judge to the pre-trial assessment. Furthermore, it has important consequences in the field of constitutional review, as the meaning of the law is determined in the process of its application.
CONTRADICTIO IN ADIECTO - OR TO WHAT EXTENT WHAT IS OBVIOUS NEEDS A LEGAL CONSTRUCTION